Dampak Sektor Perkebunan, Perikanan, dan Pariwisata terhadap Produk Domestik Bruto Bangka Belitung - ifada, zuriyat; Az-zahid, Muhammad Fawaz (Jurnal Nasional Manajemen Pemasaran dan SDM, 2025)
This study aims to analyze the impact of the plantation, fisheries, and tourism sectors on the Gross Regional Domestic Product (GRDP) of the Bangka Belitung Province, with tin export acting as a moderating variable. The research utilizes semi-annual secondary data from 2017 to 2023. A quantitative approach is applied using multiple linear regression and Moderated Regression Analysis (MRA). The results indicate that the fisheries and tourism sectors have a positive and significant effect on GRDP, whereas the plantation sector does not show a statistically significant influence. Tin export as a moderating variable significantly strengthens the relationship between the fisheries and tourism sectors and GRDP, but weakens the link between the plantation sector and GRDP. These findings suggest that tin export may function both as a catalyst and a structural distortion to domestic sectors. Therefore, inclusive and cross-sectoral economic policies are necessary to ensure balanced and sustainable regional economic growth.